2011
DOI: 10.1038/nmeth.1748
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced yeast one-hybrid assays for high-throughput gene-centered regulatory network mapping

Abstract: A major challenge in systems biology is to understand the gene regulatory networks that drive development, physiology and pathology. Interactions between transcription factors and regulatory genomic regions provide the first level of gene control. Gateway-compatible yeast one-hybrid (Y1H) assays present a convenient method to identify and characterize the repertoire of transcription factors that can bind a DNA sequence of interest. To delineate genome-scale regulatory networks, however, large sets of DNA fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
170
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(183 citation statements)
references
References 34 publications
7
170
0
Order By: Relevance
“…The promoter:HIS3 sequences were integrated into the genome of the haploid yeast (Saccharomyces cerevisiae) strain YM4271, and the pDEST-AD-CRF6 was transformed into the strain Ya1867 as previously described to create the bait and preys, respectively (Deplancke et al, 2006;Reece-Hoyes et al, 2011). The transformed haploid baits were grown on minimum selective media containing all necessary amino acids except His (synthetic dropout [SD-HT]), and the transformed haploid preys were selected on SD-T (Trp).…”
Section: Yeast One-hybridmentioning
confidence: 99%
“…The promoter:HIS3 sequences were integrated into the genome of the haploid yeast (Saccharomyces cerevisiae) strain YM4271, and the pDEST-AD-CRF6 was transformed into the strain Ya1867 as previously described to create the bait and preys, respectively (Deplancke et al, 2006;Reece-Hoyes et al, 2011). The transformed haploid baits were grown on minimum selective media containing all necessary amino acids except His (synthetic dropout [SD-HT]), and the transformed haploid preys were selected on SD-T (Trp).…”
Section: Yeast One-hybridmentioning
confidence: 99%
“…For example, Marbach et al (2012) and Beyer et al (2006) both combined coexpression data with in vivo binding data from ChIP, evolutionary conservation, and PWM models of binding specificity. The latter can be derived by several experimental methods, including protein binding arrays (Zhu et al 2009), Selex ( Jolma et al 2010), and yeast one-hybrid assays (Reece-Hoyes et al 2011). Interestingly, the analysis by Beyer et al (2006), which included a comprehensive yeast ChIP data set (Harbison et al 2004), identified only 5245 TF-target relationships that they considered ''high confidence.''…”
Section: Building a More Comprehensive Networkmentioning
confidence: 99%
“…26,42,58 The C. elegans RBP library is currently small with 40 RBPs, but we anticipate expanding this library as we have done previously for our transcription factor collection. 59 In the future, we also anticipate streamlining the PRIMA pipeline such that we can make the process higher throughput, similar to yeast one-and-two hybrid assays used for the study of protein-DNA and protein-protein interactions, respectively. 59, 60 We have not tested 3 0 UTRs longer than 437 nucleotides.…”
Section: Limitationsmentioning
confidence: 99%
“…59 In the future, we also anticipate streamlining the PRIMA pipeline such that we can make the process higher throughput, similar to yeast one-and-two hybrid assays used for the study of protein-DNA and protein-protein interactions, respectively. 59, 60 We have not tested 3 0 UTRs longer than 437 nucleotides. It is important to note that most 3 0 UTRs in C. elegans are shorter, 6 indicating that PRIMA should be broadly applicable to this organism's RNA-RBP interactome.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation